Magnetic wedge and rotating electrical machine
By using a magnetic wedge composed of a plurality of flat magnetic metal particles and inclusion phases in the rotating motor and forming a high-resistance coating on the surface, the existing magnetic wedges are solved in the high-order harmonic loss, magnetic saturation, low magnetic permeability, thermal stability and mechanical characteristics in the rotating motor, and higher magnetic permeability and efficiency are achieved.
Patent Information
- Application Number
- CN202410534689.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-21
- Filing Date
- 2024-04-30
- Publication Date
- 2025-03-21
AI Technical Summary
The existing magnetic wedges have problems in rotating motors such as high harmonic loss, magnetic saturation, low magnetic permeability, and insufficient thermal stability and mechanical characteristics.
A magnetic wedge composed of a plurality of flat magnetic metal particles and inclusion phases is used to ensure that in the cross section perpendicular to the length direction of the magnetic wedge, more than 10% of the length of the flat magnetic metal particles is arranged outside the contour average line in the width direction, and a high resistance coating layer is formed on the surface.
It improves the magnetic permeability of the magnetic wedge, reduces losses, enhances thermal stability and mechanical characteristics, and improves the efficiency of the rotating motor.
Smart Images

Figure CN119675310A_ABST
Abstract
Description
[0001] Citation of Related Applications
[0002] This application is based on Japanese Patent Application No. 2023-156244 (filing date: September 21, 2023), and claims priority based on the patent application. The present application incorporates the entire contents of the application by reference. Technical Field
[0003] Embodiments of the present invention relate to a magnetic wedge and a rotating electric machine. Background Art
[0004] Generally, the coil winding of a rotating electric machine is accommodated in the core slot and supported and fixed by a wedge-shaped piece provided at the slot opening. The material of the wedge-shaped piece is generally a non-magnetic body, but since the magnetic resistance value in the gap between the stator core and the rotor core becomes discontinuous, the magnetic flux distribution of the core surface portion opposite to the wedge-shaped piece across the gap pulsates, and the high-order harmonic loss increases. In order to reduce the high-order harmonic loss, a wedge-shaped piece (magnetic wedge) with moderate magnetism has been provided in the past. By applying the magnetic wedge, the high-order harmonic loss is reduced and the efficiency of the rotating electric machine is improved. Figure 1 It is a schematic diagram of the use state of the magnetic wedge and the effect of the magnetic wedge. Figure 1 An example of a radial gap type rotating electrical machine is shown. Figure 1 The magnetic wedge 100 , the coil 230 , the core teeth 250 , and the core slots 260 are described.
[0005] Regarding the magnetic wedge, it is self-evident that the higher the magnetic permeability of the magnetic wedge, the more it can reduce the high-order harmonic loss. Figure 1 As shown, since the magnetic wedge is configured in a manner that bridges the adjacent core teeth, there is a disadvantage that the leakage flux flowing through the core teeth through the magnetic wedge will increase. In addition, the existing magnetic wedge is prone to magnetic saturation due to its low saturation magnetization, and the efficiency improvement of the rotating motor is limited due to the large loss (large hysteresis loss due to high coercive force, large eddy current loss due to low resistivity). In addition, the existing magnetic wedge has a low magnetic permeability, so the efficiency improvement of the rotating motor is limited, and it is insufficient in terms of thermal stability and mechanical properties (strength, toughness). Therefore, it is desired to improve the characteristics of the magnetic wedge in terms of saturation magnetization, magnetic permeability, loss, strength, toughness, etc. In particular, it is desired to improve the magnetic properties, electrical properties, and thermomechanical properties. Summary of the invention
[0006] The problem to be solved by the present invention is to provide a magnetic wedge and a rotating electric machine having excellent magnetic and electrical characteristics.
[0007] The magnetic wedge of the embodiment is a magnetic wedge for a rotating electric machine, the magnetic wedge comprising a plurality of flat magnetic metal particles and an inclusion phase, and including, in a cross section perpendicular to the longitudinal direction of the magnetic wedge and at the center in the longitudinal direction: flat magnetic metal surface particles having a length of at least 10% arranged on the outside relative to an average line of a contour in the width direction of the magnetic wedge.
[0008] According to the above aspects, a magnetic wedge and a rotating electric machine having excellent magnetic and electrical characteristics are provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] Figure 1 It is a schematic diagram of the use state of the magnetic wedge and the effect of the magnetic wedge.
[0010] Figure 2 This is a conceptual diagram showing an example of a method of determining the thickness of the flat magnetic metal particles in the magnetic wedge according to the first embodiment.
[0011] Figure 3A-3C This is a conceptual diagram for explaining a method of obtaining the maximum length and the minimum length within the flat surface of the flat magnetic metal particles in the magnetic wedge according to the first embodiment.
[0012] Figure 4 This is a conceptual diagram for explaining another example of a method of obtaining the maximum length and the minimum length within the flat surface of the flat magnetic metal particles in the magnetic wedge of the first embodiment.
[0013] Figure 5 This is a schematic diagram showing the direction in which the coercive force is measured by changing the direction at intervals of 22.5 degrees with respect to the 360-degree angle within the flat surface of the flat magnetic metal particle in the magnetic wedge of the first embodiment.
[0014] Figure 6A-6B This is a schematic diagram of flat magnetic metal particles in the magnetic wedge according to the first embodiment.
[0015] Figure 7 It is a schematic diagram of the magnetic wedge according to the first embodiment.
[0016] Figure 8 It is a schematic diagram of the magnetic wedge according to the first embodiment.
[0017] Figure 9A-9B This is an example of a cross-sectional photograph of the magnetic wedge according to the first embodiment.
[0018] Fig.10 It is a schematic diagram of the magnetic wedge according to the first embodiment.
[0019] Fig.11 This is a schematic diagram showing an example of a radial gap type rotating electrical machine according to the second embodiment.
[0020] Fig.12 This is a schematic diagram showing an example of an axial gap type rotating electrical machine according to the second embodiment.
[0021] Fig.13 This is a schematic diagram showing an example of a generator according to the second embodiment.
[0022] Fig.14 This is a schematic diagram showing an example of a linear motor according to a second embodiment.
[0023] Explanation of symbols
[0024] 6: Flat surface
[0025] 9: Coating layer
[0026] 10: Flat magnetic metal particles
[0027] 20: Inclusion phase
[0028] 100: Magnetic wedge
[0029] 200: Rotating motor
[0030] 210: Rotor
[0031] 220: Stator
[0032] 222: Stator core
[0033] 230: Coil
[0034] 232: Excitation coil
[0035] 234: Armature coil
[0036] 240: Gap surface
[0037] 250: Core teeth
[0038] 260: Core slot
[0039] 270: Stator
[0040] 280: Axis
[0041] 290: Active Components DETAILED DESCRIPTION
[0042] Hereinafter, the embodiments will be described using the drawings. It should be noted that the same or similar reference numerals are used to designate the same or similar parts in the drawings. In addition, in this specification, all measurements are performed at 25° C. unless otherwise specified.
[0043] In this specification, each direction of "axial direction", "rotational direction" and "radial direction" is defined based on the rotor of the rotating electrical machine. That is, "axial direction" means the direction along the rotation axis of the rotor, and "rotational direction" means the circumferential direction around the rotation axis of the rotor (or its tangential direction). And, "radial direction" means the direction orthogonal to (perpendicularly intersecting) the rotation axis of the rotor.
[0044] (First embodiment)
[0045] The magnetic wedge of this embodiment is a magnetic wedge for a rotating electric machine, and the magnetic wedge includes a plurality of flat magnetic metal particles and an inclusion phase, and includes, in a cross section of the magnetic wedge perpendicular to its longitudinal direction and at the center in the longitudinal direction: flat magnetic metal surface particles having a length of more than 10% arranged on the outside relative to an average line of a contour in the width direction of the magnetic wedge.
[0046] The flat magnetic metal particles are flat particles (flaky particles, flattened particles) having a flaky (flaky, flattened) shape (flaky shape, flattened shape).
[0047] Thickness refers to the average thickness of a flat magnetic metal particle. As a method for calculating the thickness, any method is not limited as long as it is a method that can calculate the average thickness of a flat magnetic metal particle. For example, the following method can be used: observe the cross section of the flat magnetic metal particle perpendicular to its flat surface using a transmission electron microscope (TEM: Transmission Electron Microscopy) or a scanning electron microscope (SEM: Scanning Electron Microscopy) or an optical microscope, and select any 10 or more points along the direction within the flat surface in the cross section of the observed flat magnetic metal particle, measure the thickness of each selected point, and use the average value. In addition, the following method can also be used: in the cross section of the observed flat magnetic metal particle, select 10 or more points at equal intervals from the end toward the other end in the direction within the flat surface (in this case, the end and the other end are special positions and it is preferably not selected), measure the thickness of each selected point, and use the average value. Figure 2 This is a conceptual diagram showing an example of a method of determining the thickness of the flat magnetic metal particles in the magnetic wedge according to the first embodiment. Figure 2 The method of calculating the thickness in this case is specifically shown. 10 locations are selected at equal intervals from one end toward the other end in the direction within the flat surface (excluding the end), and the thickness of each location is t1, t2, ..., t 10 In the case of 10) / 10. It should be noted that it is preferable to measure as many positions as possible during the measurement in order to obtain average information. It should be noted that when the contour line of the cross section has a severely uneven or rough surface and it is difficult to obtain the average thickness while maintaining the original state, it is preferable to smooth the contour line with an average straight line or curve according to the situation before performing the above method.
[0048] In addition, the average thickness refers to the average value of the thickness of multiple flat magnetic metal particles, which is different from the simple "thickness" mentioned above. When calculating the average thickness, it is preferred to use the value obtained by averaging more than 20 flat magnetic metal particles. In addition, it is preferred to use as many flat magnetic metal particles as possible as the object to obtain the average information. In addition, when it is not possible to observe more than 20 flat magnetic metal particles, it is preferred to observe as many flat magnetic metal particles as possible and use the value obtained by averaging them. The average thickness of the flat magnetic metal particles is preferably greater than 10nm and less than 100μm. More preferably, it is greater than 10nm and less than 1μm, and further preferably, it is greater than 10nm and less than 100nm. In addition, the flat magnetic metal particles preferably include particles with a thickness of more than 10nm and less than 100μm, more preferably, more than 10nm and less than 1μm, and further preferably, more than 10nm and less than 100nm. Through these, when a magnetic field is applied in a direction parallel to the flat surface, the eddy current loss can be sufficiently reduced, which is preferred. In addition, when the thickness is small, the magnetic moment is limited to the direction parallel to the flat surface, and it is easy to magnetize with rotational magnetization, which is preferred. When magnetizing with rotational magnetization, it is easy to magnetize reversibly, so the coercive force becomes small, thereby reducing hysteresis loss, which is preferred.
[0049] The average length of the flat magnetic metal particles is defined as (a+b) / 2 using the maximum length a and the minimum length b within the flat surface. The maximum length a and the minimum length b can be obtained by the following operation. For example, think of the rectangle with the smallest area among the rectangles circumscribed to the flat surface. Then, the length of the long side of the rectangle is set as the maximum length a, and the length of the short side is set as the minimum length b. Figure 3A-3C This is a conceptual diagram for explaining a method of obtaining the maximum length and the minimum length within the flat surface of the flat magnetic metal particles in the magnetic wedge according to the first embodiment. Figure 3A-3CIt is a schematic diagram showing the maximum length a and the minimum length b obtained by the above method using several flat magnetic metal particles as examples. The maximum length a and the minimum length b, like the average thickness, can be obtained by observing the flat magnetic metal particles with a TEM, SEM, or optical microscope. In addition, image analysis of microscope photos can also be performed on a computer to obtain the maximum length a and the minimum length b. In either case, it is preferred to obtain the maximum length a and the minimum length b using more than 20 flat magnetic metal particles as the object. In addition, it is preferred to obtain the average information using as many flat magnetic metal particles as possible as the object. In addition, in the case where more than 20 flat magnetic metal particles cannot be observed, it is preferred to observe as many flat magnetic metal particles as possible and use the value obtained by averaging them. In addition, it is preferred to obtain the value as average as possible at this time, so it is preferred to observe or image analyze in a state where the flat magnetic metal particles are uniformly dispersed (in a state where a plurality of flat magnetic metal particles with different maximum lengths and minimum lengths are dispersed as randomly as possible). For example, it is preferable to observe or image-analyze by sticking a plurality of flat magnetic metal particles on a tape while stirring and mixing them well, or by dropping a plurality of flat magnetic metal particles from above and sticking them on a tape.
[0050] However, depending on the flat magnetic metal particles, when the maximum length a and the minimum length b are obtained by the above method, there is a possibility that the method cannot grasp the essence. Figure 4 This is a conceptual diagram for explaining another example of how to find the maximum length and the minimum length of the flat magnetic metal particles in the flat surface of the magnetic wedge of the first embodiment. Figure 4 In this case, the flat magnetic metal particles are in an elongated and curved state. In this case, the maximum length and the minimum length of the flat magnetic metal particles are essentially Figure 4 The lengths of a and b shown. Thus, the method for finding the maximum lengths a and b is not completely uniquely determined. Basically, there is no problem with the method of "thinking of the rectangle with the smallest area among the rectangles circumscribed to the flat surface, and setting the length of the long side of the rectangle as the maximum length a, and setting the length of the short side as the minimum length b". However, depending on the shape of the particles, when this method cannot grasp the essence, the maximum length a and minimum length b that grasp the essence are calculated according to circumstances. The thickness t is defined as the length in the direction perpendicular to the flat surface. The ratio A of the average length within the flat surface to the thickness is defined as A = ((a+b) / 2) / t) using the maximum length a, the minimum length b, and the thickness t.
[0051] The average value of the ratio of the average length in the flat surface of the flat magnetic metal particles to the thickness is preferably 5 or more and 10000 or less. This is because the magnetic permeability is increased and the ferromagnetic resonance frequency can be increased, thereby reducing the ferromagnetic resonance loss.
[0052] The average value is used for the ratio of the average length in the flat surface to the thickness. Preferably, the value obtained by averaging more than 20 flat magnetic metal particles is preferably used. In addition, it is preferred to use as many flat magnetic metal particles as possible as the object to obtain the information that can be averaged. In addition, when it is not possible to observe more than 20 flat magnetic metal particles, it is preferred to observe as many flat magnetic metal particles as possible and use the value obtained by averaging them. It should be noted that, for example, when there are particles Pa, particles Pb, particles Pc, each with a thickness of Ta, Tb, Tc, and an average length in the flat surface of La, Lb, Lc, the average thickness is calculated by (Ta+Tb+Tc) / 3, and the average value of the ratio of the average length in the flat surface to the thickness is calculated by (La / Ta+Lb / Tb+Lc / Tc) / 3.
[0053] The flat magnetic metal particles preferably have a coercive force difference based on direction within the flat surface. The larger the ratio of the coercive force difference based on direction, the better, and preferably it is 1% or more. More preferably, the ratio of the coercive force difference is 10% or more, further preferably, the ratio of the coercive force difference is 50% or more, and further preferably, the ratio of the coercive force difference is 100% or more. The coercive force difference ratio mentioned here refers to the maximum coercive force Hc (max) and the minimum coercive force Hc (min) defined as (Hc (max) - Hc (min)) / Hc (min) × 100 (%) within the flat surface. It should be noted that the coercive force can be evaluated using a vibrating sample magnetometer (VSM: Vibrating Sample Magnetometer) or the like. In the case of low coercive force, a coercive force of less than 0.1 Oe can also be measured by using a low magnetic field unit. The direction within the flat surface is changed relative to the direction of the measuring magnetic field for measurement.
[0054] It should be noted that "having a coercive force difference" means that when the coercive force is measured by applying a magnetic field along the 360-degree direction within the flat surface, there is a direction in which the coercive force is maximum and a direction in which the coercive force is minimum. For example, when the coercive force is measured by changing the direction at intervals of 22.5 degrees relative to the 360-degree angle within the flat surface, when a coercive force difference occurs, that is, an angle at which the coercive force becomes larger and an angle at which the coercive force becomes smaller, it is expressed as "having a coercive force difference". Figure 5Schematic diagram showing the direction of measuring the coercive force by changing the direction at intervals of 22.5 degrees with respect to the 360-degree angle within the flat surface of the flat magnetic metal particle in the magnetic wedge of the first embodiment. Figure 5 In the figure, the flat surface of the flat magnetic metal particle is illustrated as a flat surface seen from above. It is preferred that the minimum coercive force value is smaller than the isotropic case with almost no coercive force difference by having a coercive force difference in the flat surface. In a material having magnetic anisotropy in the flat surface, the coercive force has a difference depending on the direction in the flat surface, and the minimum coercive force value is smaller than the magnetic isotropic material. This reduces the hysteresis loss and improves the magnetic permeability, which is preferred. Figure 5 Flat magnetic metal particles 10 and flat surfaces 6 are shown.
[0055] In addition, the flat magnetic metal particles have a magnetic metal phase containing at least one first element selected from the group consisting of Fe, Co and Ni. It should be noted that the flat magnetic metal particles contain Fe and Co, and the amount of Co is preferably greater than 10 atomic % and less than 60 atomic % relative to the total amount of Fe and Co, and is further preferably contained in an amount of greater than 10 atomic % and less than 40 atomic %. This makes it easy to impart a large magnetic anisotropy appropriately, and the above-mentioned magnetic properties are improved, so it is preferred. In addition, the Fe-Co system easily achieves high saturation magnetization, so it is preferred. Furthermore, by making the composition range of Fe and Co fall within the above range, a higher saturation magnetization can be achieved, which is preferred.
[0056] Elements can be easily analyzed by EDX (Energy Dispersive X-ray spectroscopy), ICP (Inductively Coupled Plasma) emission spectroscopy, or the like.
[0057] The flat magnetic metal particles preferably contain at least one non-magnetic metal selected from the group consisting of Mg, Al, Si, Ca, Zr, Ti, Hf, Zn, Mn, Ba, Sr, Cr, Mo, Ag, Ga, Sc, V, Y, Nb, Pb, Cu, In, Sn, and rare earth elements. Thus, the thermal stability and oxidation resistance of the flat magnetic metal particles can be improved. Among them, Al and Si are particularly preferred because they are easily dissolved in Fe, Co, and Ni, which are the main components of the flat magnetic metal particles, and contribute to improving thermal stability and oxidation resistance.
[0058] It should be noted that in order to induce magnetic anisotropy, there is also the following method: the crystallinity of the flat magnetic metal particles is amorphized as much as possible, and magnetic anisotropy is induced in one direction in the plane by using magnetic field and strain. In this case, it is ideal to make the flat magnetic metal particles as easy to amorphize as possible. From this point of view, the magnetic metal contained in the flat magnetic metal particles preferably includes at least one additive element selected from B (boron), Si (silicon), Al (aluminum), C (carbon), Ti (titanium), Zr (zirconium), Hf (hafnium), Nb (niobium), Ta (tantalum), Mo (molybdenum), Cr (chromium), Cu (copper), W (tungsten), P (phosphorus), N (nitrogen), Ga (gallium), and Y (yttrium). It is preferred that the difference in atomic radius between at least one first element selected from the group consisting of Fe, Co, and Ni is large. In addition, it is preferred that the negative value of the mixing enthalpy of at least one first element selected from the group consisting of Fe, Co, and Ni and the additive element becomes large. In addition, it is preferred to use a multi-element system formed by a total of more than three elements including the first element and the additional element. In addition, since the added elements of semimetals such as B and Si slow down the crystallization rate and are easy to become amorphous, it is beneficial if they are mixed into the system. From the above point of view, B, Si, P, Ti, Zr, Hf, Nb, Y, Cu, etc. are preferred, and it is more preferred that the added element includes any one of B, Si, Zr, Hf, and Y. As an example, it is preferred that the first element as the magnetic metal phase includes Fe and Co, and the added elements include Si and B. In addition, the total amount of the aforementioned additional elements is preferably contained at 0.001 atomic % or more and 80 atomic % or less relative to the total amount of the aforementioned first element and the aforementioned additional elements. It is more preferably 5 atomic % or more and 80 atomic % or less, and it is further preferred that it is 10 atomic % or more and 40 atomic % or less. It should be noted that the greater the total amount of the aforementioned added elements, the easier it is to amorphize and impart magnetic anisotropy, so it is preferred (i.e., it is preferred from the perspective of low loss and high magnetic permeability), but on the other hand, the ratio of the magnetic metal phase decreases, so the saturation magnetization decreases, which is not preferred in this regard. Based on the above situation, it is important to comprehensively consider high saturation magnetization, low loss, high magnetic permeability, etc. to select the composition and the amount of added elements.
[0059] The flat magnetic metal particles preferably have at least a portion of their surface covered with a coating layer having a thickness of 0.1 nm to 1 μm inclusive and containing at least one second element selected from the group consisting of oxygen (O), carbon (C), nitrogen (N), and fluorine (F).
[0060] Figure 6A-6B Schematic diagram of the flat magnetic metal particles in the magnetic wedge according to the first embodiment. The coating layer 9 and the flat magnetic metal particles 10 are shown.
[0061] The coating layer more preferably comprises at least one non-magnetic metal selected from the group consisting of Mg, Al, Si, Ca, Zr, Ti, Hf, Zn, Mn, Ba, Sr, Cr, Mo, Ag, Ga, Sc, V, Y, Nb, Pb, Cu, In, Sn, and rare earth elements, and comprises at least one second element selected from the group consisting of oxygen (O), carbon (C), nitrogen (N), and fluorine (F). As non-magnetic metals, Al and Si are particularly preferred from the perspective of thermal stability. In the case where the flat magnetic metal particles comprise at least one non-magnetic metal selected from the group consisting of Mg, Al, Si, Ca, Zr, Ti, Hf, Zn, Mn, Ba, Sr, Cr, Mo, Ag, Ga, Sc, V, Y, Nb, Pb, Cu, In, Sn, and rare earth elements, the coating layer more preferably comprises at least one non-magnetic metal identical to the non-magnetic metal as one of the constituent components of the flat magnetic metal particles. Among oxygen (O), carbon (C), nitrogen (N) and fluorine (F), oxygen (O) is preferably included, preferably an oxide or a composite oxide. The above is from the perspective of the ease of formation of the coating layer, oxidation resistance, and thermal stability. Through the above method, the close adhesion between the flat magnetic metal particles and the coating layer can be improved, and the thermal stability and oxidation resistance of the magnetic wedge described later can be improved. The coating layer can not only improve the thermal stability and oxidation resistance of the flat magnetic metal particles, but also improve the electrical resistance of the flat magnetic metal particles. By increasing the resistance, eddy current loss can be suppressed and the frequency characteristics of the magnetic permeability can be improved. Therefore, the coating layer is preferably high-resistance, for example, preferably has a resistance value of 1 mΩ·cm or more.
[0062] In addition, the presence of a coating layer is also preferred from a magnetic point of view. Flat magnetic metal particles can be regarded as approximate thin films because their thickness is relatively small relative to the size of the flat surface. At this time, the structure obtained by forming a coating layer on the surface of the flat magnetic metal particles for integration can be regarded as an approximate stacked film structure, and the magnetic domain structure is energetically stabilized. As a result, the coercive force can be reduced (thereby reducing the hysteresis loss), which is preferred. At this time, the magnetic permeability also becomes larger, which is preferred. From this point of view, the coating layer is more preferably non-magnetic (the magnetic domain structure becomes easy to stabilize).
[0063] The thickness of the coating layer is preferably thicker from the perspective of thermal stability, oxidation resistance, and electrical resistance. However, if the thickness of the coating layer becomes too thick, the saturation magnetization becomes smaller, and thus the magnetic permeability also becomes smaller, which is not preferred. In addition, from the perspective of magnetism, if the thickness becomes too thick, the "effects of stabilizing the magnetic domain structure, reducing coercive force, reducing loss, and increasing magnetic permeability" are reduced. Considering the above, the preferred thickness of the coating layer is greater than 0.1 nm and less than 1 μm, and more preferably greater than 0.1 nm and less than 100 nm.
[0064] The inclusion phase contains at least one second element selected from the group consisting of oxygen (O), carbon (C), nitrogen (N) and fluorine (F). This is because the electrical resistance can be increased. The resistivity of the inclusion phase is preferably higher than the resistivity of the flat magnetic metal particles. This can reduce the eddy current loss of the flat magnetic metal particles. Since the inclusion phase exists surrounding the flat magnetic metal particles, it is possible to improve the oxidation resistance and thermal stability of the flat magnetic metal particles, which is preferred. Among them, the inclusion phase containing oxygen is more preferred from the perspective of high oxidation resistance and high thermal stability. The inclusion phase also plays the role of mechanically bonding the flat magnetic metal particles, so it is also preferred from the perspective of high strength.
[0065] The inclusion phase preferably includes resin. As resin, thermoplastic resin, thermosetting resin, polyester resin, vinyl ester resin, polyethylene resin, polystyrene resin, polyvinyl chloride resin, polyvinyl butyral resin, polyvinyl alcohol resin, polybutadiene resin, Teflon (registered trademark) resin, polyurethane resin, cellulose resin, ABS resin, nitrile rubber, styrene-butadiene rubber, silicone resin, other synthetic rubbers, natural rubber, epoxy resin, phenolic resin, allyl resin, polybenzimidazole resin, amide resin, polyimide resin, polyamide-imide resin, bismaleimide resin or their copolymers can be used. In particular, in order to achieve high thermal stability, it is preferred to include silicone resin, polyimide resin, imide resin, bismaleimide resin with high heat resistance. Epoxy resin, phenolic resin, polyester resin are commonly used resins with high heat resistance and high strength, and are preferred. In addition, it is preferred to contain at least one resin selected from the group consisting of bismaleimide resins, polyimide resins, polyester resins, phenolic resins, epoxy resins, and silicone resins. In addition, after exposure to the atmosphere at 120°C for 30 minutes, the weight increase rate after exposure to the atmosphere at room temperature for 1 week is preferably 1% or less, and more preferably 0.1% or less. In addition, the water absorption rate specified in ISO 62:1999 (JIS K7209:2000) is preferably 1% or less, and more preferably 0.1% or less. In addition, in order to improve the strength, it is also preferred to mix glass fiber, aramid fiber, carbon fiber, Zylon fiber, polyethylene fiber, boron fiber and other fibers such as FRP (Fiber-Reinforced Plastics: fiber reinforced plastics) and other materials. Through the above method, the bonding between the flat magnetic metal particles and the inclusion phase becomes firm, and the mechanical properties such as thermal stability, strength, and toughness become easy to improve. In addition, the inclusion phase surrounds the flat magnetic particles, which makes the oxidation resistance excellent and the magnetic properties are not easily degraded by oxidation of the flat magnetic metal particles. It should be noted that the type of resin can be identified by IR (Infrared Spectroscopy), NMR (Nuclear Magnetic Resonance), etc.
[0066] Bismaleimide resins are preferred because they can be molded at a relatively low temperature (e.g., below 180°C) during molding, and can therefore be molded using a commonly used low-temperature hot press apparatus. In addition, as properties after molding, high thermal stability and excellent mechanical properties can be achieved, so they are preferred. Furthermore, it is easy to compound (join) with flat magnetic metal particles, and it is also easy to achieve excellent mechanical properties such as thermal stability, strength, and toughness as a composite material, so it is preferred. In addition, the inclusion phase easily surrounds the flat magnetic particles, and it is not easy for the magnetic properties to deteriorate due to oxidation of the flat magnetic metal particles, so it is preferred.
[0067] The bismaleimide resin preferably has a glass transition temperature of 250° C. or higher. This is preferred because thermal stability, strength, and the like are improved.
[0068] The bismaleimide resin preferably includes 4,4'-diphenylmethane bismaleimide, phenylmethane maleimide, m-phenylene bismaleimide, bisphenol A diphenyl ether bismaleimide, 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide, 4-methyl-1,3-phenylene bismaleimide, 1,6'-bismaleimide-(2,2,4-trimethyl)hexane, 2,2'-diallyl bisphenol A, 4 ,4'-diphenyl ether bismaleimide, 4,4'-diphenyl sulfone bismaleimide, 1,3-bis(3-maleimide phenoxy)benzene, 1,3-bis(4-maleimide phenoxy)benzene, bis(3-ethyl-5-methyl-4-maleimide phenyl)methane, 2,2'-bis[4-(4-maleimide phenoxy)phenyl]propane, etc. (Since these monomers are polymerized to make bismaleimide resins, it is preferred to include the above substances in the form of monomers). As a result, thermal stability, strength, etc. are improved, which becomes preferred.
[0069] In addition, the curing agent for curing the monomer preferably includes 4,4'-diaminodiphenylmethane, diaminodiphenyl ether, diaminodiphenyl sulfone, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, o,o'-diallylbisphenol A, etc. However, the curing agent may be other types as long as it can appropriately cure the monomer.
[0070] As a preferred combination of a monomer and a curing agent, for example, 4,4'-diphenylmethane bismaleimide and 4,4'-diaminodiphenylmethane can be cited. In addition, when 4,4'-diphenylmethane bismaleimide and 4,4'-diaminodiphenylmethane are included, the ratio of 4,4'-diphenylmethane bismaleimide to 4,4'-diaminodiphenylmethane is preferably 1 to 3, and more preferably about 2. The above ratio is preferred because thermal stability, strength, etc. are improved.
[0071] The molecular weight of the inclusion phase is preferably 100 to 1000. This is preferred because thermal stability, strength, and the like are improved.
[0072] The polyimide resin preferably contains a repeating unit represented by the following chemical formula (1).
[0073]
[0074] In the chemical formula (1), R preferably includes any of the structures of biphenyl, triphenyl and tetraphenyl. R' preferably represents a structure having at least one aromatic ring in the structure.
[0075] Furthermore, as the polyimide resin, it is more preferable to have the structural formula (2) or (3) below.
[0076]
[0077] Figure 7 FIG. 1 is a schematic diagram of a magnetic wedge according to the present embodiment. Figure 7 As shown, the cross-section may be not only a simple rectangular parallelepiped shape (rectangular shape), but also a trapezoidal shape, a hexagonal shape, a convex shape, and other shapes. The closer the magnetic wedge is to the gap surface between the rotor and the stator, the more effective it is (the effect of improving the efficiency of the rotating electric machine). Therefore, from this point of view, the trapezoidal shape, the convex shape, and the hexagonal shape are more preferred than the rectangular shape. In addition, from the perspective of "a shape that is easy to introduce magnetic flux to the magnetic wedge side (thereby making it easy to improve the efficiency of the rotating electric machine)", the trapezoidal shape and the convex shape are more preferred than the hexagonal shape. On the other hand, from the perspective of ease of manufacturing and the height of reliability as a material (mechanical properties, thermal properties), the rectangular shape is most preferred, followed by the trapezoidal shape and the hexagonal shape. In this sense, the trapezoidal shape is easy to be arranged close to the gap surface between the rotor and the stator, and the magnetic flux is easy to be introduced to the magnetic wedge side by the trapezoidal shape, which is easy to manufacture and easy to improve the reliability as a material (mechanical properties, thermal properties), so it is very preferred.
[0078] It should be noted that, regardless of the shape, three axial directions that are orthogonal or perpendicular to each other are defined as the width direction, the thickness direction, and the length direction. The length direction of the magnetic wedge refers to the direction in which the length of the magnetic wedge is long. For example, when the shape of the magnetic wedge as the object is a substantially rectangular parallelepiped shape, the direction along the longest side of the substantially rectangular parallelepiped shape is determined as the length direction of the magnetic wedge as the object. The thickness direction and the width direction of the magnetic wedge refer to directions orthogonal to the length direction of the magnetic wedge. The thickness direction and the width direction of the magnetic wedge can be distinguished as follows. When the magnetic wedge as the object is set in a rotating electric machine, the magnetic wedge as the object is taken out from the inside of the rotating electric machine. Here, the rotation direction of the rotating electric machine is the width direction of the magnetic wedge as the object. The thickness direction is a direction perpendicular to the width direction. On the other hand, when the magnetic wedge as the object is not set in the rotating electric machine, the direction closest to the average orientation direction of the flat magnetic metal particles in the center of the cross section perpendicular to the length direction is the width direction. The thickness direction is a direction perpendicular to the width direction. It should be noted that, with respect to the cross section perpendicular to the length direction, the end face of the magnetic wedge as the object is avoided. The cross section is cut perpendicularly to the length direction of the magnetic wedge as the object so as to have a length of at least 1 / 10 of the length of the magnetic wedge as the object in the length direction. In addition, as the center of the cross section formed by the cutting, for example, a region containing a plurality of flat magnetic metal particles is used at the geometric center of the cross section. Next, in the magnetic wedge as the object, the cross section formed by the cutting is observed using an optical microscope, SEM, or TEM. Then, for each flat magnetic metal particle observed in the cross section formed by the cutting, a rectangle with the smallest area among rectangles circumscribing each flat magnetic metal particle is thought out, and the direction of the long side direction of the rectangle is measured as the orientation direction. However, the flat magnetic metal particles may include particles whose outlines are unclear during observation and difficult to evaluate. That is, sometimes the outline of the particle cannot be clearly determined in image analysis, and this case is excluded from the observation object.
[0079] Figure 8: is a schematic diagram of a magnetic wedge of the present embodiment. It shows flat magnetic metal particles existing near the contour line in the width direction in a cross section perpendicular to the length direction of the magnetic wedge and at the center of the length direction (hereinafter, the characteristics are defined based on this cross section), and flat magnetic metal particles existing closer to the center of the magnetic wedge. It should be noted that as a method for obtaining the cross section perpendicular to the length direction of the magnetic wedge and at the center of the length direction, the method is not limited as long as the size, contour line, etc. of the flat magnetic metal particles can be obtained. For example, observation is performed using a scanning electron microscope (SEM: Scanning Electron Microscopy) or an optical microscope or a transmission electron microscope (TEM: Transmission Electron Microscopy), etc., and observation is performed at any magnification. Here, the flat magnetic metal particles that are closest to the contour line in the width direction are referred to as flat magnetic metal surface particles. In addition, the contour average line in the width direction is an average line obtained by averaging the concave and convex state of the contour line in the width direction. The contour average line can be defined as the "average line" in the surface roughness measurement of JIS-B0601 (ISO-4287), etc. In the magnetic wedge of the present embodiment, it is preferred that the cross section of the magnetic wedge perpendicular to the longitudinal direction and at the center of the longitudinal direction contains flat magnetic metal surface particles whose lengths are arranged outside the average line of the contours in the width direction by 10% or more of the flat magnetic metal particles. It is more preferred that the cross section of the magnetic wedge perpendicular to the longitudinal direction and at the center of the longitudinal direction contains flat magnetic metal surface particles whose lengths are arranged outside the average line of the contours in the width direction of the magnetic wedge by 10% or more of the flat magnetic metal surface particles, preferably 1% or more and 90% or less, more preferably 5% or more and 60% or less, and even more preferably 5% or more and 30% or less of the total number of flat magnetic metal surface particles present in the measured cross section.
[0080] In a cross section of the magnetic wedge perpendicular to its longitudinal direction and at the center of the longitudinal direction, the orientation angle of the flat magnetic metal surface particles whose length is more than 10% arranged on the outside than the average line of the contour in the width direction of the magnetic wedge is preferably greater than 1 degree and less than 60 degrees, more preferably greater than 3 degrees and less than 45 degrees, and even more preferably greater than 3 degrees and less than 30 degrees, relative to the average line of the contour in the width direction.
[0081] As an example of flat magnetic metal surface particles in which 10% or more of the length is arranged outside the average line of the outline in the width direction of the magnetic wedge, Figure 8Flat magnetic metal surface particles A and B are shown. Both flat magnetic metal surface particles A and B are contour average lines based on the width direction of the magnetic wedge, and 10% or more of the length of the flat magnetic metal particles exists outside the contour average line. A portion of the flat magnetic metal surface particle A is arranged to protrude outside the magnetic wedge, and the flat magnetic metal particle B is arranged in the inclusion phase without protruding outside the magnetic wedge. Any of the flat magnetic metal surface particles A and B is preferred.
[0082] The flat magnetic metal particles of the magnetic wedge have the above-mentioned configuration structure, so that the surface roughness is moderately rough. The surface roughness Ra of the magnetic wedge is greater than 0.1 μm and less than 100 μm, more preferably greater than 0.1 μm and less than 10 μm, and further preferably greater than 1 μm and less than 10 μm. It should be noted that, preferably, the contour line in the width direction of the cross section of the magnetic wedge perpendicular to its length direction and at the center of the aforementioned length direction (i.e., the surface in the width direction) preferably satisfies the surface roughness within this range, more preferably, the surface including the width direction and the length direction in the magnetic wedge satisfies the surface roughness within this range, and further preferably, any surface of the magnetic wedge satisfies the surface roughness within this range. It should be noted that the surface roughness Ra and its measurement method are defined by JIS-B0601 (ISO-4287).
[0083] By having the above structure (arrangement structure, number ratio, orientation angle, surface roughness, etc. of flat magnetic metal surface particles), it is possible to efficiently guide magnetic flux in the rotating electric machine, improve the magnetic permeability and efficiency of the rotating electric machine, so it is preferred. Regarding the magnetic permeability, the magnetic permeability in the direction between the width direction and the thickness direction of the magnetic wedge is improved, so it is preferred. In addition, the loss in the direction between the width direction and the thickness direction of the magnetic wedge is also reduced, which is also preferred.
[0084] Furthermore, by having the above-described structure, when a surface coating layer for protecting the magnetic wedge is further provided, an anchoring effect can be obtained, so that the coating layer can be firmly formed. This improves the reliability of the material, which is preferred. For example, it is preferred that excellent properties can be maintained without deteriorating the strength after the heat resistance test and the efficiency as a rotating electric machine.
[0085] FIG. 9 is an example of a cross-sectional photograph of a magnetic wedge according to the present embodiment. Fig. 9A , Fig. 9B Examples are shown. Fig. 9AThe diagram shows flat magnetic metal particles with an orientation angle of 23 degrees and 64% of their length arranged outside the average contour line in the width direction, flat magnetic metal particles with an orientation angle of 14 degrees and 62% of their length arranged outside the average contour line in the width direction, and flat magnetic metal particles with an orientation angle of 15 degrees and 79% of their length arranged outside the average contour line in the width direction. Fig. 9B The flat magnetic metal particles with an orientation angle of 5 degrees and 27% of the length are arranged outside the average line of the profile in the width direction, and the flat magnetic metal particles with an orientation angle of 8 degrees and 23% of the length are arranged outside the average line of the profile in the width direction are shown. These are examples of flat magnetic metal surface particles in which more than 10% of the length of the flat magnetic metal particles is arranged outside the average line of the profile in the width direction. In addition, the orientation angle of these flat magnetic metal surface particles is greater than 1 degree and less than 60 degrees (also satisfying greater than 3 degrees and less than 30 degrees) relative to the average line of the profile in the width direction.
[0086] Fig.10 Schematic diagram of a magnetic wedge according to this embodiment. Fig.10 In this case, at least a portion of the surface of the magnetic wedge is covered by the surface coating layer. In this case, it is more preferred if at least a portion of the flat magnetic metal surface particles is covered by the surface coating layer. Figure 8 At least a portion of the flat magnetic metal surface particles A is covered with the surface coating layer.
[0087] The thickness of the surface coating layer is preferably greater than the average thickness of the aforementioned flat magnetic metal surface particles, and more preferably greater than the average length of the aforementioned flat magnetic metal particles. It is further preferably greater than the maximum length of the aforementioned flat magnetic metal particles. By having the above structure, the surface coating layer can be firmly fitted (bonded) with the magnetic wedge (anchoring effect) to protect the magnetic wedge, so it is preferred. As a result, the reliability of the material can be improved, so it is preferred. For example, by the presence of the coating layer, the resistivity can be greatly improved, so when used as a magnetic wedge, electrical short circuits can be suppressed, and eddy current losses can be reduced and the efficiency of the rotating motor can be improved, so it is preferred. In addition, it is preferred that excellent properties can be maintained without deteriorating the strength after the heat resistance test and the efficiency as a rotating motor. In addition, it is preferred that the oxidation of flat magnetic metal particles and flat magnetic metal surface particles can be suppressed, and excellent magnetic properties (saturation magnetization, coercive force, magnetic permeability) can be maintained.
[0088] The surface coating layer preferably comprises inorganic materials such as oxide, carbide, nitride, boride, and organic materials such as resin, more preferably comprises resin.As resin, thermoplastic resin, thermosetting resin, polyester resin, vinyl ester resin, polyethylene resin, polystyrene resin, polyvinyl chloride resin, polyvinyl butyral resin, polyvinyl alcohol resin, polybutadiene resin, Teflon (registered trademark) resin, polyurethane resin, cellulose resin, ABS resin, acrylonitrile-butadiene rubber, styrene-butadiene rubber, silicone resin, other synthetic rubbers, natural rubber, epoxy resin, phenolic resin, allyl resin, polybenzimidazole resin, amide resin, polyimide resin, polyamide-imide resin, bismaleimide resin or their copolymer can be used.Particularly to realize high thermal stability, preferably comprise silicone resin, polyimide resin, imide resin, bismaleimide resin with high heat resistance. Epoxy resin, phenolic resin, polyester resin are commonly used resins with high heat resistance and high strength, and are preferred. In addition, it is preferred to include at least one resin selected from the group consisting of bismaleimide resin, polyimide resin, polyester resin, phenolic resin, epoxy resin, and silicone resin.
[0089] As mentioned above, the type of resin can be identified by IR, NMR, etc. In addition, after exposure to the atmosphere at 120°C for 30 minutes, the weight increase rate after exposure to the atmosphere at room temperature for one week is preferably 1% or less, and more preferably 0.1% or less. In addition, the water absorption rate specified in ISO 62:1999 (JIS K7209:2000) is preferably 1% or less, and more preferably 0.1% or less. Preliminary investigations have shown that in a magnetic wedge formed of flat magnetic metal particles and an inclusion phase, especially when the inclusion phase is a resin, once water and moisture are absorbed, the weight increases, and mechanical properties such as strength are easily deteriorated. In addition, once the flat magnetic metal particles absorb water and moisture, they also oxidize, the saturation magnetization and magnetic permeability decrease, and the loss increases, which is not preferred. Therefore, it is considered effective to prevent the inclusion phase from contacting water and moisture as much as possible (suppressing weight increase). In this embodiment, by coating the surface of the magnetic wedge with a surface coating layer with low water absorption and hygroscopicity, the inclusion phase can be prevented from contacting water and moisture as much as possible. This prevents mechanical properties such as strength from being degraded and allows excellent properties to be maintained. In addition, since oxidation of the flat magnetic metal particles is also suppressed, saturation magnetization, magnetic permeability, and loss are not degraded and allow excellent properties to be maintained.
[0090] A method for manufacturing a magnetic wedge according to the present embodiment will be described. It should be noted that the manufacturing method is not particularly limited, and is described merely as an example.
[0091] The first step is a step of manufacturing a magnetic metal ribbon containing at least one first element selected from the group consisting of Fe, Co, and Ni. This step is, for example, a step of using a film forming device such as a roller quenching device and a sputtering device to make a thin ribbon or a film. At this time, in the film forming method using the film forming device, it is ideal to form a film that imparts uniaxial anisotropy to the film surface by film forming in a magnetic field, rotary film forming, etc. It should be noted that when a film forming device is used, a product with a thin thickness and a refined structure is easily formed, and rotational magnetization is easy to occur. Therefore, when a product of a rotational magnetization type is manufactured, it is ideal to use a film forming method. The roller quenching device is suitable for mass synthesis, so it is ideal when synthesizing bulk materials. For the roller quenching device, a single roller quenching device is simple and preferred.
[0092] The second step is a step of heat treating the magnetic metal strip at a temperature of 50°C or more and 800°C or less. In order to facilitate the placement of the strip in the electric furnace for heat treatment, the strip can be cut into a suitable size in this step. For example, a stirring device (mixer) or the like can be used to cut the strip into a suitable size. By performing this step, the crushing property becomes easy to improve in the next third step, i.e., the crushing step, which is ideal. It should be noted that the heat treatment atmosphere is ideally a vacuum atmosphere with a low oxygen concentration, an inactive atmosphere, or a reducing atmosphere, and further ideally and preferably a reducing atmosphere such as H2 (hydrogen), CO (carbon monoxide), or CH4 (methane). The reason for this is that even if the magnetic metal strip is oxidized, the oxidized metal can be reduced and restored to metal by heat treatment in a reducing atmosphere. Thus, the magnetic metal strip that has been oxidized and has reduced saturation magnetization can be reduced, and the saturation magnetization can also be restored. It should be noted that, in the case of an amorphous composition, if the crystallization of the magnetic metal strip is significantly carried out by heat treatment, an increase in coercivity and a decrease in magnetic permeability will occur, so it is preferred to select conditions to suppress excess crystallization. In addition, it is more preferred and more desirable to implement heat treatment in a magnetic field. The larger the applied magnetic field, the more preferred it is, preferably applying more than 1kOe, and further more preferably applying more than 10kOe. Thus, the magnetic metal strip can exhibit magnetic anisotropy in the plane, and excellent magnetic properties can be achieved, so it is preferred.
[0093] The third step is a step of crushing the heat-treated magnetic metal strip to produce flat magnetic metal particles. It should be noted that in this step, a stirring device or the like can be used to cut the magnetic metal strip or film into a suitable size before the main crushing. In this step, crushing is performed using a crushing device such as a bead mill or a planetary grinder, for example. It should be noted that the type of crushing device is not limited. For example, a planetary grinder, a bead mill, a rotary ball mill, a vibrating ball mill, a stirring ball mill (grinding machine), a jet mill, a centrifuge, or a method of combining a mill with a centrifugal separation can be listed. When crushing, if the crushing is performed while cooling at a temperature below 0°C, the crushing is easy to perform, which is preferred. It is particularly desirable to cool at liquid nitrogen temperature (77K), dry ice temperature (194K), etc., and it is particularly desirable to cool to liquid nitrogen temperature. As a result, the magnetic metal strip is prone to low-temperature brittleness and is easy to crush. That is, it is possible to crush efficiently without applying excessive stress or strain to the magnetic metal strip, so it is preferred. However, in many cases, the pulverization can be sufficiently performed without cooling, and in such a case, cooling is not necessary.
[0094] It should be noted that in the third step, not only is crushing performed simply, but rolling can also be combined to make the thickness of the flat magnetic metal particles thinner. It should be noted that, in the case where a specified thickness has been formed by the second step, the treatment for rolling can be omitted. Here, rolling can be performed simultaneously, or rolling can be performed after crushing, or crushing can be performed after rolling. In this case, it is preferred that a device capable of applying a strong gravitational acceleration be used, such as a planetary grinder, a bead mill, a rotary ball mill, a vibrating ball mill, a stirring ball mill (grinding mill), a jet mill, a centrifuge, or a method of combining a mill with a centrifugal separation. For example, a high-power planetary grinder device is preferred because it can simply apply a gravitational acceleration of tens of G. In the case of a high-power planetary grinder device, it is more preferred that the direction of the rotational gravitational acceleration and the direction of the revolution gravitational acceleration are not directions on the same straight line but form an inclined planetary grinder device with an angled direction. The direction of the gravity acceleration of the rotation of the conventional planetary grinding machine is on the same straight line as the direction of the gravity acceleration of the revolution, while the inclined planetary grinding machine performs a rotational motion when the container is tilted, so the direction of the gravity acceleration of the rotation and the direction of the gravity acceleration of the revolution are not on the same straight line and form a direction with an angle. Thus, the power is efficiently transmitted to the sample, and the crushing and rolling are efficiently performed, so it is preferred. In addition, considering mass production, it is preferred to be a bead mill device that is easy to process in large quantities.
[0095] It is desirable to perform the above-mentioned cutting, crushing, and rolling (rolling is performed as needed. If not necessary, it is not performed), and the cutting, crushing, and rolling are repeated as needed to form flat magnetic metal particles of a predetermined thickness and aspect ratio. At this time, if the crushing and rolling are performed to a thickness of 10 nm to 100 μm, more preferably 10 nm to 1 μm, and further preferably 10 nm to 100 nm, particles that are easily magnetized by rotation are formed, which is preferred.
[0096] In order to achieve the orientation degree of the flat magnetic metal particles as in the present embodiment, it is effective to improve the sliding property of the flat magnetic metal particles and to increase the fluidity. Therefore, the average thickness of the flat magnetic metal particles is preferably 10 μm or more and 30 μm or more, more preferably 10 μm or more and 20 μm or less, and the average value of the ratio of the average length to the thickness of the flat magnetic metal particles is preferably 10 or more and 100 or less, more preferably 10 or more and 50 or less.
[0097] In addition, it is desirable that the obtained flat magnetic metal particles are heat treated to appropriately remove lattice distortion. The heat treatment at this time is preferably carried out at a temperature of 50°C or more and 800°C or less, as in the second step, and the heat treatment atmosphere is preferably a vacuum atmosphere with a low oxygen concentration, an inactive atmosphere, or a reducing atmosphere, and it is further desirable and preferred to be a reducing atmosphere such as H2, CO, or CH4. In addition, it is more preferred and more desirable to perform the heat treatment in a magnetic field. The reasons and details for these are the same as those for the second step, so the description is omitted here.
[0098] Next, as the fourth step, the inclusion phase is mixed with magnetic metal particles to form a mixed powder of the inclusion phase and flat magnetic metal particles. Next, as the fifth step, the mixed powder of the inclusion phase and the magnetic metal particles is molded. In addition, heat treatment can be appropriately performed before or after the above steps. That is, heat treatment can be performed before or after molding or simultaneously with molding. In addition, heat treatment can be performed before or after processing. The heat treatment conditions are as described above. In addition, it is more preferred and more ideal to perform heat treatment in a magnetic field. The reasons and details about these are the same as those for the second step, so the description is omitted here.
[0099] In order to obtain the magnetic wedge of the present embodiment, the fifth step becomes very important. The fifth step preferably adopts a method of applying pressing pressure in a uniaxial direction, such as uniaxial pressing molding and hot pressing molding. If pressing pressure is applied in a uniaxial direction, the flat magnetic metal particles are easily stacked and oriented in the direction of application of the pressing pressure. Therefore, if it is a simple uniaxial pressing molding, the flat magnetic metal particles will be stacked and oriented in the direction of application of the pressing pressure, that is, in one direction, which is not preferred. Therefore, it is preferred to apply a magnetic field in a direction parallel to the direction of application of the pressing pressure when applying the pressing pressure in the uniaxial direction. In addition, it is also preferred to magnetize the die punch during molding in a direction parallel to the direction of application of the pressing pressure. Through these, it becomes easy for the flat magnetic metal particles to move in a direction parallel to the direction of application of the pressing pressure, so it becomes easy to synthesize "a magnetic wedge containing flat magnetic metal surface particles whose length is more than 10% arranged on the outside than the average line of the contour in the width direction of the aforementioned magnetic wedge". In addition, by adjusting the magnetic field application conditions, mold state, and pressing conditions at this time, the "ratio of the flat magnetic metal surface particles whose length is more than 10% arranged on the outside of the average line of the contour in the width direction of the magnetic wedge to the total number of flat magnetic metal surface particles" can be adjusted.
[0100] In addition, it is preferred to perform hot pressing after uniaxial pressing. In the case where the inclusion phase is, for example, a thermosetting resin, it is preferred to adjust the hot pressing temperature and time during hot pressing and stop before the inclusion phase solidifies. It should be noted that, in hot pressing, it is more preferred to perform hot pressing while applying a magnetic field in a direction parallel to the direction in which the pressing pressure is applied. As a result, it is easier for the flat magnetic metal particles to move in a direction parallel to the direction in which the pressing pressure is applied, and it is therefore easier to synthesize a "magnetic wedge containing flat magnetic metal surface particles whose length is more than 10% arranged to the outside than the average line of the contour in the width direction of the magnetic wedge". In addition, in hot pressing, it is also preferred to reduce or release the pressing pressure when the resin softens or melts. As a result, it is preferred that the flat magnetic metal particles move in a direction parallel to the direction in which the pressing pressure is applied. With regard to the hot pressing temperature, it is preferably performed at a temperature of 50°C or more and 1000°C or less, and more preferably at a temperature of 50°C or more and 800°C or less. The larger the applied magnetic field, the better, and it is preferred to apply 1 kOe or more, and more preferably 10 kOe or more. The pressing pressure is preferably 1 MPa or more and 100 MPa or less, more preferably 1 MPa or more and 10 MPa or less. Then, preferably, heat treatment is performed while applying a magnetic field in a direction parallel to the direction of application of the pressing pressure to completely solidify it. Regarding the heat treatment temperature, it is preferably performed at a temperature of 50°C or more and 1000°C or less, more preferably 50°C or more and 800°C or less. The larger the applied magnetic field, the more preferred, preferably 1 kOe or more, more preferably 10 kOe or more.
[0101] By adjusting the hot pressing temperature and time, the "ratio of the flat magnetic metal surface particles whose length is 10% or more arranged outside the average line of the contour in the width direction of the magnetic wedge to the total number of flat magnetic metal surface particles" can be adjusted. For example, in the case where it is desired to increase the "ratio of the flat magnetic metal surface particles whose length is 10% or more arranged outside the average line of the contour in the width direction of the magnetic wedge to the total number of flat magnetic metal surface particles", it can be adjusted by lowering the hot pressing temperature or shortening the hot pressing time. By lowering the hot pressing temperature or shortening the hot pressing time, the solidification of the inclusion phase is incomplete, and the flat magnetic metal particles are in a state where they are easy to move. As a result, after hot pressing, when heat treatment is performed while applying a magnetic field in a direction parallel to the direction in which the pressing pressure is applied, the flat magnetic metal particles become easy to move in a direction parallel to the direction in which the pressing pressure is applied (gradually solidify while moving), and as a result, after the inclusion phase is completely solidified, the "ratio of the flat magnetic metal surface particles whose length is 10% or more arranged outside the average line of the contour in the width direction of the magnetic wedge to the total number of flat magnetic metal surface particles" increases. On the contrary, if it is desired to reduce "the ratio of the flat magnetic metal surface particles whose length is 10% or more arranged outside the average line of the contour in the width direction of the magnetic wedge to the total number of the flat magnetic metal surface particles", it can be adjusted by making the hot pressing temperature higher or extending the hot pressing time. By making the hot pressing temperature higher or extending the hot pressing time, the solidification of the inclusion phase is further advanced, and the flat magnetic metal particles are in a state where it is difficult to move. Therefore, after hot pressing, when heat treatment is performed while applying a magnetic field in a direction parallel to the direction of application of the pressing pressure, it becomes difficult for the flat magnetic metal particles to move in a direction parallel to the direction of application of the pressing pressure (gradually solidifying in a state where it is difficult to move), and as a result, after the inclusion phase is completely solidified, "the ratio of the flat magnetic metal surface particles whose length is 10% or more arranged outside the average line of the contour in the width direction of the magnetic wedge to the total number of the flat magnetic metal surface particles" is reduced. It should be noted that even when the inclusion phase is a thermoplastic resin or an oxide having a softening point, the same magnetic wedge can be manufactured by improving the molding process. That is, the same magnetic wedge can be manufactured regardless of the type of the inclusion phase. For example, when the resin softens and melts during hot pressing, the same magnetic wedge can be manufactured by reducing or releasing the pressing pressure, applying a magnetic field in a direction parallel to the direction of pressing pressure application, or lowering the temperature in this state to solidify the resin.
[0102] Next, in the sixth step, a surface coating layer is formed on the surface of the formed magnetic wedge. In this step, an inorganic material or an organic material is coated on the surface of the magnetic wedge. The coating method is not particularly limited. When coating an organic material such as a resin, it is also preferable to coat it by an impregnation method, a dipping method, etc., or to press it by hot pressing or the like after coating, depending on the situation. When coating an inorganic material, it is also preferable to coat it by a gas phase method, a liquid phase method such as a sol-gel, etc., or to press it by hot pressing or the like after coating, depending on the situation. In addition, it is also preferable to perform a heat treatment after coating to form a strong coating layer.
[0103] When measuring the coercive force based on direction in a plane parallel to the flat surface of the flat magnetic metal particles of the magnetic wedge, the coercive force is measured by changing the direction at intervals of 22.5 degrees with respect to an angle of 360 degrees in the plane.
[0104] By having a coercive force difference in the aforementioned plane of the magnetic wedge, the minimum coercive force value becomes smaller than the isotropic case with almost no coercive force difference, which is preferable. In a material having magnetic anisotropy in a plane, the coercive force is made different depending on the direction in the plane, and the minimum coercive force value becomes smaller than the magnetic isotropic material. This reduces the hysteresis loss and improves the magnetic permeability, which is preferable.
[0105] The larger the ratio of the coercive force difference based on the direction in the plane parallel to the flat surface of the flat magnetic metal particles possessed by the magnetic wedge, the better, and preferably 1% or more. More preferably, the ratio of the coercive force difference is 10% or more, further preferably, the ratio of the coercive force difference is 50% or more, and further preferably, the ratio of the coercive force difference is 100% or more. The ratio of the coercive force difference mentioned here is defined as (Hc(max)-Hc(min)) / Hc(min)×100(%) using the maximum coercive force Hc(max) and the minimum coercive force Hc(min) in the flat surface.
[0106] It should be noted that the coercive force can be simply evaluated using a vibrating sample magnetometer (VSM) or the like. In the case of low coercive force, a coercive force of 0.1 Oe or less can also be measured by using a low magnetic field unit. The measurement is performed by changing the direction of the magnetic field in the aforementioned plane of the magnetic wedge (in the plane parallel to the flat surface of the flat magnetic metal particle) relative to the direction of the measurement magnetic field.
[0107] When calculating the coercive force, the value obtained by dividing the difference between the magnetic fields at two points intersecting the horizontal axis (magnetic fields H1 and H2 where magnetization is zero) by 2 can be used (that is, it can be calculated as coercive force = |H2-H1| / 2).
[0108] As described above, according to the present embodiment, the magnetic wedge is a magnetic wedge for a rotary electric machine, the magnetic wedge includes a plurality of flat magnetic metal particles and an inclusion phase, and includes a flat magnetic metal surface particle having 10% or more of its length arranged outside the average line of the contour in the width direction of the magnetic wedge in a cross section perpendicular to the longitudinal direction of the magnetic wedge and at the center in the longitudinal direction. Thus, a magnetic wedge having excellent magnetic properties such as high magnetic permeability and low loss, excellent mechanical properties such as strength, and excellent thermomechanical properties such as excellent magnetic properties and mechanical properties even after a heat resistance test can be provided.
[0109] (Second embodiment)
[0110] The rotating electrical machine of this embodiment includes the magnetic wedge of the first embodiment. Therefore, the contents overlapped with those of the first embodiment are omitted. In this specification, the rotating electrical machine is a concept including a motor, a generator, and an electric generator that performs the functions of both a motor and a generator as required.
[0111] Fig.11 This is an example of a radial gap type motor according to the present embodiment. The radial gap type motor includes a rotor and a stator which is arranged to face the rotor with a predetermined gap in the radial direction. Fig.11 In the embodiment, the rotor is arranged inside the stator, but it may be arranged outside. The rotor includes a rotor core and a shaft, and is supported in a rotatable manner. On the other hand, the stator includes a stator core, a field coil inserted in a slot of the stator core, and a magnetic wedge held in a wedge groove at an opening of the slot. Fig.11 An example in which the magnetic wedges of the first embodiment are arranged is shown, but the present invention is not limited thereto. In the case of a radial gap type rotating electrical machine, the stator is arranged relative to the rotor at a predetermined interval in the radial direction, so the "gap surface" is a surface parallel to the cylindrical surface centered on the rotating axis of the rotor. Therefore, the radial direction is a direction perpendicular to the gap surface, and the axial direction and the rotation direction are directions parallel to the gap surface. Fig.11 Flat magnetic metal particles 10 , inclusion phases 20 , magnetic wedges 100 , a rotating electrical machine 200 , a rotor 210 , a stator 220 , a coil 230 , a gap surface 240 , and core teeth 250 are shown.
[0112] By configuring the magnetic wedge of the first embodiment, it is possible to suppress leakage flux and reduce the harmonic loss generated on the rotor surface. In addition, since the magnetic flux passing through the gap increases, the torque of the radial gap type motor increases. By either or both of the above loss reduction effect and torque increase effect, high efficiency can be achieved.
[0113] The radial gap motor may be any of a motor having a conductor on the rotor (induction motor), a motor having a permanent magnet (permanent magnet motor), and a motor having a magnetic body (reluctance motor).
[0114] Fig.12 This is an example of an axial gap type motor of the present embodiment. The axial gap type motor has a rotor and a stator arranged relative to the rotor with a predetermined gap in the axial direction, and the stator has a stator core, a field coil inserted in the slot of the stator core, and a magnetic wedge held in the wedge groove of the slot opening. By configuring the magnetic wedge of the present embodiment, the increase of leakage flux can be suppressed and the reduction of high-order harmonic loss generated on the surface of the rotor can be achieved. In addition, since the magnetic flux passing through the gap increases, the torque of the axial gap type motor increases. Through the above method, high efficiency can be achieved. Fig.12 In the embodiment, the rotor is arranged between two stators, but it may be arranged on one side or both sides of a stator. In the case of an axial gap type rotating electric machine, since the stator is arranged relative to the rotor at a predetermined interval in the axial direction, the "gap surface" is a surface orthogonal to the rotation axis of the rotor. Therefore, the axial direction is a direction perpendicular to the gap surface, and the rotation direction and radial direction are directions parallel to the gap surface. Fig.12 Flat magnetic metal particles 10 , inclusion phases 20 , magnetic wedges 100 , a rotating electrical machine 200 , a rotor 210 , a coil 230 , a gap surface 240 , core teeth 250 , a stator 270 , and a shaft 280 are shown.
[0115] Fig.13 : is a schematic diagram showing an example of a generator of the present embodiment. The generator generally has a rotor that accommodates an excitation coil in a slot of a rotor core (in addition, a rotor that uses a permanent magnet as an excitation source may be used), and a stator that accommodates an armature coil in a slot of a stator core, so that the rotor rotates and an excitation current flows into the excitation coil, thereby generating power in the armature coil. The rotor includes a rotor core, a field coil inserted in a slot of the rotor core, and a magnetic wedge held in a wedge groove at an opening of the slot, and is supported by a bearing in a rotatable manner. By configuring the magnetic wedge of the present embodiment, the increase in leakage flux can be suppressed and the higher harmonic loss generated on the surface of the stator can be reduced. In addition, since the amount of magnetic flux that passes through the gap and interlinks with the armature coil increases, the power generation voltage caused by the armature coil increases. By the above method, high efficiency can be achieved. Fig.13 In the embodiment, the magnetic wedges are arranged at the slot opening of the rotor core, but they may be arranged at the slot opening of the stator core. In addition, the figure shows a winding type generator in which the rotor has an excitation coil, but it may also be a permanent magnet type generator in which the rotor has a permanent magnet. In this case, the magnetic wedges are arranged at the slot opening of the stator core. Fig.13Flat magnetic metal particles 10 , inclusion phases 20 , magnetic wedges 100 , a rotating electrical machine 200 , a rotor 210 , a stator core 222 , a field coil 232 , an armature coil 234 , a gap surface 240 , and core teeth 250 are shown.
[0116] A linear motor is a flat plate-shaped structure obtained by developing a radial gap type motor, so the magnetic wedge of the present invention can also be applied to a linear motor. That is, the stator includes a stator core and a field coil inserted in a slot of the stator core, and the magnetic wedge can be provided at the slot opening. Fig.14 : is a schematic diagram showing an example of a linear motor of the present embodiment. In the linear motor, the moving direction of the active element, the direction at right angles to the moving direction of the active element, and the direction perpendicular to the stator correspond to the rotation direction, axial direction, and radial direction of the radial gap type motor, respectively. By configuring the magnetic wedge of the present embodiment, the increase of leakage flux can be suppressed and the reduction of high-order harmonic loss generated on the surface of the active element can be achieved. In addition, since the magnetic flux passing through the gap increases, the thrust of the linear motor is improved. By the above method, high efficiency can be achieved. Fig.14 Flat magnetic metal particles 10 , an inclusion phase 20 , a magnetic wedge 100 , a stator 220 , a coil 230 , a gap surface 240 , a core tooth 250 , and a moving element 290 are shown.
[0117] As described above, according to the rotary electric machine of this embodiment, the increase of leakage magnetic flux caused by the use of magnetic wedges can be suppressed, and the pulsation of magnetic flux distribution on the surface of the core can be effectively alleviated, so that high efficiency can be achieved. It should be noted that the slot shape of the rotary electric machine of this embodiment can be a semi-closed slot (or semi-closed slot), preferably an open slot (or open slot). In this case, the high-order harmonic loss can be greatly reduced, which is preferred.
[0118] The rotating electric machine of this embodiment can be applied to transportation systems such as railways, electric vehicles, and hybrid vehicles, social systems such as elevators and air conditioners, industrial systems such as robots, pumps, compressors, and blowers, energy systems such as thermal generators, hydroelectric generators, wind generators, nuclear power generators, and geothermal generators, and home appliances such as washing machines, and can achieve high efficiency of the system. In particular, large-capacity machines for industrial use generally have slots as the slot shape, so it is preferable to have the magnetic wedge of the first embodiment. In addition, active motors for railways use type-wound coils based on the need to withstand high voltages and vibrations, and the slot shape is slotted, so it is preferable to have the magnetic wedge of the first embodiment.
[0119] For railways, since the loss of rotating electric machines accounts for about half of the power consumption when the railway is running, the effect of improving efficiency by reducing the loss of rotating electric machines is very large. In addition, for electric vehicles and hybrid vehicles, the efficiency of the active motor can be improved by using the magnetic wedge of the first embodiment, thereby increasing the cruising range.
[0120] Among generators, a great effect can be expected for a hydroelectric generator, particularly a variable speed pumped storage generator. In addition, a great effect can also be expected for a wind power generator.
[0121] Example
[0122] Hereinafter, Examples 1 to 4 will be described in more detail while comparing Comparative Examples 1 and 2.
[0123] (Example 1)
[0124] First, a thin strip of Fe-Co-Si-B (Fe70Co30B25 (atomic %) -4wt% Si) is made using a single-roll quenching device. Next, the obtained thin strip is heat treated at 300°C in an H2 atmosphere. Next, the thin strip is crushed using a stirring device to obtain flat magnetic metal particles (average thickness is about 15μm, and the average value of the ratio of the average length in the flat surface to the thickness is about 30). Then, the obtained flat magnetic metal particles are mixed with a bismaleimide resin and molded. During molding, when a pressing pressure is applied in a uniaxial direction, a magnetic field is applied in a direction parallel to the direction in which the pressing pressure is applied. Then, hot pressing is performed. During hot pressing, the hot pressing temperature and time are adjusted and stopped before solidification occurs. Then, heat treatment is performed while applying a magnetic field in a direction parallel to the direction in which the pressing pressure is applied to completely solidify it and produce a magnetic wedge. It should be noted that by adjusting the hot pressing temperature and time, the ratio of the flat magnetic metal surface particles having more than 10% of their length arranged outside the average contour line of the width direction of the magnetic wedge to the total number of the flat magnetic metal surface particles is adjusted, which is 1% in the present embodiment 1.
[0125] (Example 2)
[0126] The hot pressing temperature and time were adjusted so that the ratio of flat magnetic metal surface particles having at least 10% of their length arranged outside the average contour line of the magnetic wedge in the width direction to the total number of flat magnetic metal surface particles was 20%, and the method was substantially the same as in Example 1 except that the ratio was 20%.
[0127] (Example 3)
[0128] The hot pressing temperature and time were adjusted so that the ratio of flat magnetic metal surface particles having at least 10% of their length arranged outside the average contour line in the width direction of the magnetic wedge to the total number of flat magnetic metal surface particles was 50%, and the method was substantially the same as in Example 1 except that the ratio was 50%.
[0129] (Example 4)
[0130] The hot pressing temperature and time were adjusted so that the ratio of flat magnetic metal surface particles having at least 10% of their lengths arranged outside the average contour line of the magnetic wedge in the width direction to the total number of flat magnetic metal surface particles was 90%, and the method was substantially the same as in Example 1 except that the ratio was 90%.
[0131] (Comparative Example 1)
[0132] The process was substantially the same as in Example 1 except that the heat treatment was performed while applying a magnetic field in a direction perpendicular to the direction of application of the pressing pressure after the complete solidification was performed during the hot press molding. At this time, there were no flat magnetic metal surface particles having a length of 10% or more arranged outside the average contour line in the width direction of the magnetic wedge.
[0133] (Comparative Example 2)
[0134] The hot pressing temperature and time were adjusted so that the ratio of flat magnetic metal surface particles having at least 10% of their lengths arranged outside the average contour line of the width direction of the magnetic wedge to the total number of flat magnetic metal surface particles was 95%, and the method was substantially the same as in Example 1 except that the ratio was 95%.
[0135] Table 1 shows the ratio of the flat magnetic metal surface particles of which 10% or more of the length is arranged outside the average line of the widthwise contour of the magnetic wedge to the total number of the flat magnetic metal surface particles in the magnetic wedge of the present embodiment together with Comparative Examples 1 and 2.
[0136] Table 2 shows the magnetic permeability of the magnetic wedge according to the present embodiment, the degree of improvement in efficiency as a rotating electrical machine, the magnetic permeability after a heat resistance test, the degree of improvement in efficiency as a rotating electrical machine, the magnetic permeability of the sample after the surface coating after a heat resistance test, the degree of improvement in efficiency as a rotating electrical machine, and the strength together with Comparative Examples 1 and 2.
[0137] (1) Magnetic permeability: The magnetic permeability at 100 Hz in the middle direction between the width direction and the thickness direction of the magnetic wedge was measured. The magnetic permeability was expressed as a ratio based on the magnetic permeability of Comparative Example 1.
[0138] (2) Efficiency improvement of the rotating electrical machine: The efficiency improvement was calculated using the efficiency when a standard radial gap motor was used as the motif and a non-magnetic wedge as the reference. The efficiency improvement was expressed as a ratio using the efficiency improvement in Comparative Example 1 as the reference.
[0139] (3) Magnetic permeability after heat resistance test: The magnetic permeability (magnetic permeability at 100 Hz in the direction between the width direction and the thickness direction of the magnetic wedge) after heating at 250°C in the atmosphere for 1000 hours (heat resistance test) was measured and expressed as a ratio to the magnetic permeability of the sample of Comparative Example 1 after heating at 250°C in the atmosphere for 1000 hours (=magnetic permeability of the evaluation sample after heating at 250°C in the atmosphere for 1000 hours / magnetic permeability of Comparative Example 1 after heating at 250°C in the atmosphere for 1000 hours).
[0140] (4) Efficiency improvement after heat resistance test: The efficiency improvement after heating at 250°C in air for 1000 hours (heat resistance test) was calculated. The efficiency improvement was expressed as a ratio based on the efficiency improvement of Comparative Example 1.
[0141] (5) Magnetic permeability of surface-coated sample after heat resistance test: A surface coating layer based on a bismaleimide resin was formed on the evaluation sample, and the magnetic permeability (magnetic permeability at 100 Hz in the direction between the width direction and the thickness direction of the magnetic wedge) after heating at 250°C in the atmosphere for 1000 hours (heat resistance test) was measured. The ratio was expressed as the magnetic permeability of the sample of Comparative Example 1 after heating at 250°C in the atmosphere for 1000 hours (=magnetic permeability of the evaluation sample after heating at 250°C in the atmosphere for 1000 hours / magnetic permeability of Comparative Example 1 after heating at 250°C in the atmosphere for 1000 hours).
[0142] (6) Efficiency improvement of the sample after surface coating after heat resistance test: For the evaluation sample, a surface coating layer based on bismaleimide resin was formed, and the efficiency improvement after heating at 250°C in the atmosphere for 1000 hours (heat resistance test) was calculated. The efficiency improvement was expressed as a ratio based on the efficiency improvement in Comparative Example 1.
[0143] (7) Strength of surface-coated samples after heat resistance test: For the evaluation samples, a surface coating layer based on bismaleimide resin was formed, and the flexural strength at 25°C was measured after heating at 250°C in the atmosphere for 1000 hours (heat resistance test). The strength was expressed as the ratio to the flexural strength at 25°C of the sample of Comparative Example 1 after heating at 250°C in the atmosphere for 1000 hours (= flexural strength at 25°C of the evaluation sample after heating at 250°C in the atmosphere for 1000 hours / flexural strength at 25°C of Comparative Example 1 after heating at 250°C in the atmosphere for 1000 hours).
[0144] Table 1
[0145]
[0146] Table 2
[0147]
[0148] As shown in Table 2, Examples 1 to 4 have excellent properties in terms of magnetic permeability, degree of improvement in efficiency as a rotating electric machine, magnetic permeability after a heat test, degree of improvement in efficiency as a rotating electric machine, magnetic permeability of the sample after a heat test, degree of improvement in efficiency as a rotating electric machine, and strength compared to Comparative Examples 1 to 2. This is considered to be because the flat magnetic metal surface particles, which are arranged outside the average contour line in the width direction of the magnetic wedge for more than 10% of the length, are included in an amount of 1% to 90% relative to the total number of the flat magnetic metal surface particles, and thus the magnetic flux can be efficiently guided in the rotating electric machine (magnetic permeability and efficiency improvement). In addition, it can be seen that by having such a structure, the surface coating layer based on the resin is firmly formed, thereby maintaining excellent properties without deteriorating the strength after a heat test, magnetic permeability, and efficiency as a rotating electric machine. On the other hand, in Comparative Examples 1 and 2, the flat magnetic metal surface particles of which 10% or more of the length of the flat magnetic metal particles is arranged outside the average line of the outline in the width direction of the magnetic wedge are 0% and 95% relative to the total number of the flat magnetic metal surface particles, and the ease of conducting the magnetic flux is deteriorated, and the degree of improvement in magnetic permeability and efficiency is lower than that of Examples 1 to 4. In addition, in Comparative Examples 1 and 2, the magnetic permeability after the heat resistance test and the degree of improvement in efficiency as a rotating electric machine are also lower than those of Examples 1 to 4. Furthermore, it can be seen that in Comparative Examples 1 and 2, the surface coating layer based on the resin is not firmly formed, so the strength after the heat resistance test and the magnetic permeability and the efficiency as a rotating electric machine are deteriorated, and the characteristics are lower than those of Examples 1 to 4.
[0149] Several embodiments and examples of the present invention have been described, but these embodiments and examples are given as examples and are not intended to limit the scope of the invention. These new embodiments can be implemented in various other ways, and various omissions, substitutions, and changes can be made without departing from the gist of the invention. These embodiments and their variations fall within the scope and gist of the invention, and fall within the invention described in the claims and the scope of their equivalents.
[0150] It should be noted that the above implementation modes can be summarized as the following technical solutions.
[0151] (Technical Solution 1)
[0152] A magnetic wedge is a magnetic wedge for a rotating electric machine, the magnetic wedge comprising a plurality of flat magnetic metal particles and an inclusion phase.
[0153] In a cross section of the magnetic wedge perpendicular to its length direction and at the center of the length direction,
[0154] The plurality of flat magnetic metal particles include flat magnetic metal surface particles of which 10% or more of the length of the flat magnetic metal particles is arranged outside a mean line of the contour in the width direction of the magnetic wedge.
[0155] (Technical Solution 2)
[0156] According to the magnetic wedge described in technical solution 1, wherein, in the cross section of the magnetic wedge perpendicular to its longitudinal direction and at the center of the longitudinal direction, the flat magnetic metal surface particles having more than 10% of the length arranged on the outside than the average line of the contour in the width direction of the magnetic wedge account for more than 1% and less than 90% of the total number of the flat magnetic metal surface particles.
[0157] (Technical Solution 3)
[0158] According to the magnetic wedge described in Technical Solutions 1 to 2, wherein, in a cross section of the magnetic wedge perpendicular to its longitudinal direction and at the center of the longitudinal direction, the orientation angle of the flat magnetic metal surface particles that are arranged more than 10% of the length on the outside than the average line of the contour in the width direction of the magnetic wedge is greater than 1 degree and less than 60 degrees relative to the average line of the contour in the width direction.
[0159] (Technical Solution 4)
[0160] The magnetic wedge according to any one of claims 1 to 3, wherein the surface roughness Ra of a contour line in the width direction of a cross section perpendicular to the longitudinal direction of the magnetic wedge and at the center in the longitudinal direction is 0.1 μm or more and 100 μm or less.
[0161] (Technical Solution 5)
[0162] The magnetic wedge according to any one of claims 1 to 4, wherein at least a portion of the surface of the magnetic wedge is covered with a surface coating layer.
[0163] (Technical Solution 6)
[0164] The magnetic wedge according to claim 5, wherein the thickness of the surface coating layer is greater than or equal to the average thickness of the flat magnetic metal particles.
[0165] (Technical Solution 7)
[0166] The magnetic wedge according to any one of claims 1 to 6, wherein the inclusion phase exists between the plurality of flat magnetic metal particles and contains at least one second element selected from the group consisting of oxygen (O), carbon (C), nitrogen (N) and fluorine (F).
[0167] (Technical Solution 8)
[0168] The magnetic wedge according to any one of claims 1 to 7, wherein the inclusion phase contains a resin.
[0169] (Technical Solution 9)
[0170] The magnetic wedge according to any one of claims 1 to 8, wherein the inclusion phase includes at least one resin selected from the group consisting of bismaleimide resins, polyimide resins, polyester resins, phenolic resins, epoxy resins, and silicone resins.
[0171] (Technical Solution 10)
[0172] The magnetic wedge according to any one of claims 5 to 9, wherein the surface coating layer contains a resin.
[0173] (Technical Solution 11)
[0174] The magnetic wedge according to any one of claims 5 to 10, wherein the surface coating layer is a resin having a weight increase rate of 1% or less after exposure to an atmosphere of 120°C for 30 minutes and after exposure to an atmosphere of room temperature for one week.
[0175] (Technical Solution 12)
[0176] The magnetic wedge according to any one of claims 5 to 11, wherein the surface coating layer has a water absorption rate of 1% or less as specified in ISO 62:1999 (JIS K7209:2000).
[0177] (Technical Solution 13)
[0178] The magnetic wedge according to any one of claims 5 to 12, wherein the surface coating layer includes at least one resin selected from the group consisting of bismaleimide resins, polyimide resins, polyester resins, phenolic resins, epoxy resins, and silicone resins.
[0179] (Technical Solution 14)
[0180] A magnetic wedge according to any one of Technical Solutions 1 to Technical Solutions 13, wherein the plurality of flat magnetic metal particles have a magnetic metal phase having an average thickness of 10 nm to 100 μm inclusive and containing at least one first element selected from the group consisting of Fe, Co and Ni, and an average value of a ratio of an average length within a flat surface to the thickness is 5 to 10,000 inclusive.
[0181] (Technical Solution 15)
[0182] A magnetic wedge according to any one of Technical Solutions 1 to 14, wherein at least a portion of the surface of the flat magnetic metal particles is covered with a coating layer having a thickness of 0.1 nm to 1 μm and containing at least one second element selected from the group consisting of oxygen (O), carbon (C), nitrogen (N) and fluorine (F).
[0183] (Technical Solution 16)
[0184] The magnetic wedge according to any one of claims 1 to 15, wherein there is a coercive force difference based on a direction within the flat surface of the flat magnetic metal particle.
[0185] (Technical Solution 17)
[0186] The magnetic wedge according to any one of claims 1 to 16, wherein the magnetic wedge has a coercive force difference based on a direction in a plane parallel to the flat surface.
[0187] (Technical Solution 18)
[0188] A rotating electrical machine comprises the magnetic wedge described in any one of claims 1 to 17.
Claims
1. A magnetic wedge, which is a magnetic wedge of a rotating electrical machine, comprising a plurality of flat magnetic metal particles and an inclusion phase, In a cross section of the magnetic wedge perpendicular to its length direction and at the center of the length direction, The plurality of flat magnetic metal particles include flat magnetic metal surface particles of which 10% or more of the length of the flat magnetic metal particles is arranged outside the average line of the contour in the width direction of the magnetic wedge.
2. The magnetic wedge according to claim 1, wherein: In a cross section of the magnetic wedge perpendicular to its longitudinal direction and at the center of the longitudinal direction, the flat magnetic metal surface particles having more than 10% of the length arranged outside the average contour line of the magnetic wedge in the width direction account for more than 1% and less than 90% of the total number of the flat magnetic metal surface particles.
3. The magnetic wedge according to claim 1, wherein: In a cross section of the magnetic wedge perpendicular to its longitudinal direction and at the center of the longitudinal direction, the orientation angle of the flat magnetic metal surface particles that are arranged more than 10% of the length on the outside than the average contour line of the magnetic wedge in the width direction is greater than 1 degree and less than 60 degrees relative to the average contour line in the width direction.
4. The magnetic wedge according to claim 1, wherein: The surface roughness Ra of the outline of the width direction of the magnetic wedge in a cross section perpendicular to the longitudinal direction and at the center in the longitudinal direction is 0.1 μm or more and 100 μm or less.
5. The magnetic wedge according to claim 1, wherein: At least a portion of the surface of the magnetic wedge is covered by a surface coating layer.
6. The magnetic wedge according to claim 5, wherein: The thickness of the surface coating layer is equal to or greater than the average thickness of the flat magnetic metal particles.
7. The magnetic wedge according to claim 1, wherein: The inclusion phase exists between the plurality of flat magnetic metal particles and contains at least one second element selected from the group consisting of oxygen (O), carbon (C), nitrogen (N), and fluorine (F).
8. The magnetic wedge according to claim 1, wherein: The inclusion phase includes a resin.
9. The magnetic wedge according to claim 1, wherein: The inclusion phase includes at least one resin selected from the group consisting of bismaleimide resins, polyimide resins, polyester resins, phenolic resins, epoxy resins, and silicone resins.
10. The magnetic wedge according to claim 5, wherein: The surface coating layer contains a resin.
11. The magnetic wedge according to claim 5, wherein: The surface coating layer is a resin having a weight increase rate of 1% or less after exposure to air at 120° C. for 30 minutes and after exposure to air at room temperature for one week.
12. The magnetic wedge according to claim 5, wherein: The water absorption of the surface coating layer as specified in ISO 62:1999 or JIS K7209:2000 is 1% or less.
13. The magnetic wedge according to claim 5, wherein: The surface coating layer includes at least one resin selected from the group consisting of bismaleimide resins, polyimide resins, polyester resins, phenolic resins, epoxy resins, and silicone resins.
14. The magnetic wedge according to claim 1, wherein: The plurality of flat magnetic metal particles have an average thickness of 10 nm to 100 μm inclusive and include a magnetic metal phase containing at least one first element selected from the group consisting of Fe, Co, and Ni, and an average value of a ratio of an average length in a flat surface to the thickness is 5 to 10,000 inclusive.
15. The magnetic wedge of claim 1, wherein: At least a portion of the surface of the flat magnetic metal particle is covered with a coating layer having a thickness of 0.1 nm to 1 μm and containing at least one second element selected from the group consisting of oxygen (O), carbon (C), nitrogen (N), and fluorine (F).
16. The magnetic wedge of claim 1, wherein: The flat magnetic metal particles have a coercive force difference depending on the direction within the flat surface.
17. The magnetic wedge of claim 1, wherein: There is a direction-dependent coercive force difference in a plane parallel to the flat surface. 18 . A rotating electrical machine comprising the magnetic wedge according to claim 1 .